Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/ecc.12394
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being and quality of life among Icelanders receiving palliative care: data from Icelandic pilot-testing of a provisional measure of spiritual well-being from the European Organisation for Research and Treatment of Cancer

Abstract: Palliative care focuses on improving quality of life (QoL). This study examined the feasibility of the Icelandic version of a provisional European Organisation for Research and Treatment of Cancer (EORTC) measure of spiritual well-being (SWB), and explored the relationship between SWB and QoL for palliative care patients in Iceland. Instruments from the EORTC were used: the provisional measure of SWB, which was undergoing pilot-testing in Iceland, and the EORTC QLQ C15-PAL. The correlation between scores was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 18 publications
3
28
2
3
Order By: Relevance
“…Health professionals have an important role in enhancing psycho-spiritual well-being, although we lack the evidence for specific interventions in this area. Asgeirsdottir et al (2017) have examined this issue, in an Icelandic population; in common with other studies they have demonstrated a positive association between markers of spiritual well-being and quality of life in cancer patients.…”
Section: In Our March 2017 Issue Of Ejcc…mentioning
confidence: 72%
See 1 more Smart Citation
“…Health professionals have an important role in enhancing psycho-spiritual well-being, although we lack the evidence for specific interventions in this area. Asgeirsdottir et al (2017) have examined this issue, in an Icelandic population; in common with other studies they have demonstrated a positive association between markers of spiritual well-being and quality of life in cancer patients.…”
Section: In Our March 2017 Issue Of Ejcc…mentioning
confidence: 72%
“…Asgeirsdottir et al. () have examined this issue, in an Icelandic population; in common with other studies they have demonstrated a positive association between markers of spiritual well‐being and quality of life in cancer patients.…”
mentioning
confidence: 79%
“…In another study, conducted with 30 Icelanders patients, the quality of life was positively correlated to spiritual well-being (29) . Recent comprehensive review also identified that spiritual dimension is an essential component of palliative care to the patient, because it promotes well-being through relief of pain and other symptoms (30) .…”
Section: Discussionmentioning
confidence: 94%
“…Research nurses were instructed to mark items that the patient asked for clari cation on or indicated their inability to answer. Because the EORTC SWB32 measure has been found to prompt re ection (19) , additional time was allowed for an open discussion on issues related to spirituality. Finally, the EORTC QLQ-C30 was completed by participants.…”
Section: Methodsmentioning
confidence: 99%